A model of swādhyāya chikitsā for healthy mind and cognitive restructuring - HEMADRI K. SAO; ABHISHEK K. BHARDWAJ; GAURAV AGRAWAL (Dr. Chinmay Pandya, 2013)
Observation of present scenario indicates that the root cause of widely spread sufferings, distress and mental problems is certainly the distorted, directionless & unfocused thinking. Those who are unable to manage themselves, always live in stress, that in its consequences leads the person towards mental disorders. For mental and physical fitness level one would have to learn the art of self-management; but it is possible only after knowing the self and refining it. Understanding one's own self and refining would require proper training, guidance and therapy. As there are not enough skillful guides, so one to one guidance is not possible. The solution for this is called "Swadhyaya chikitsa". It can play a vital role as a therapy. In modern psychology the assumptions of humanistic and existential (phenomenology) therapies come very close to it. It includes the cognitive restructuring in its process of therapy, but this therapy goes beyond normal cognitive therapy as the insights developed here are far more stable and naturally implemented.